1997
DOI: 10.1128/jb.179.13.4305-4310.1997
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a monooxygenase from Streptomyces coelicolor A3(2) involved in biosynthesis of actinorhodin: purification and characterization of the recombinant enzyme

Abstract: The oxidation of phenols to quinones is an important reaction in the oxidative tailoring of many aromatic polyketides from bacterial and fungal systems. Sequence similarity between ActVA-Orf6 protein from the actinorhodin biosynthetic cluster and the previously characterized TcmH protein that is involved in tetracenomycin biosynthesis suggested that ActVA-Orf6 might catalyze this transformation as a step in actinorhodin biosynthesis. To investigate the role of ActVA-Orf6 in this oxidation, we have expressed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 36 publications
6
74
0
Order By: Relevance
“…Our work has focused on the tailoring enzymes of these pathways, particularly those catalysing the oxidations that introduce hydroxy or quinone functionality to the polyketide molecules (Kendrew et al, 1995(Kendrew et al, , 1997. We have reported the expression, puri®cation and biochemical characterization of the enzyme ActVA-Orf6 (Kendrew et al, 1997), a monooxygenase from the actinorhodin pathway that catalyses the oxidation of phenolic compounds (or their keto tautomers) to the corresponding quinone (Fig.…”
Section: Crystallization Papersmentioning
confidence: 99%
See 3 more Smart Citations
“…Our work has focused on the tailoring enzymes of these pathways, particularly those catalysing the oxidations that introduce hydroxy or quinone functionality to the polyketide molecules (Kendrew et al, 1995(Kendrew et al, , 1997. We have reported the expression, puri®cation and biochemical characterization of the enzyme ActVA-Orf6 (Kendrew et al, 1997), a monooxygenase from the actinorhodin pathway that catalyses the oxidation of phenolic compounds (or their keto tautomers) to the corresponding quinone (Fig.…”
Section: Crystallization Papersmentioning
confidence: 99%
“…We have reported the expression, puri®cation and biochemical characterization of the enzyme ActVA-Orf6 (Kendrew et al, 1997), a monooxygenase from the actinorhodin pathway that catalyses the oxidation of phenolic compounds (or their keto tautomers) to the corresponding quinone (Fig. 1).…”
Section: Crystallization Papersmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Furthermore, PnxH showed less similarity to a cofactor-independent monooxygenase SnoaB (46%) in nogalamycin biosynthesis. 27 The crystal structure of SnoaB revealed that the completely conserved tryptophan residue in this family of antibiotic monooxygenases including ActVA-Orf6, 28,29 TcmH 30 and AknX 31 is catalytically important. 32 Indeed, the corresponding tryptophan residue is conserved in PnxH, supporting its involvement in quinone formation.…”
Section: Cloning Of Fd-594 Biosynthetic Gene Cluster F Kudo Et Almentioning
confidence: 99%